Про один з поглядів на джерела та історію пізньоантичного Херсонеса - Піоро, І.С. (Археологія, 1997)
Статтю присвячено розгляду концепції К. Цукермана про деякі дискусійні питання історії пізньоантичного Херсонеса. В четвертом выпуске сборника «Материалы по археологии, истории и этнографии Таврии» (1994 г.) опубликована статья К. Цукермана о епископах и гарнизоне Херсонеса в IV в. Анализ источников (синаксарная статья от 22 декабря и список участников II Вселенского собора 381 г.) позволил К. Цукерману уточнить легендарные данные «Житий святых епископов Херсонских», передвинув время их деятельности на несколько десятилетий вперед. Однако эти выводы нельзя считать оригинальными, поскольку проблема в отечественной историографии разрабатывалась еще И. Франко, а в последние десятилетия была освещена в более чем десяти научных работах, о существовании которых К. Цукерман не осведомлен.
Рассматривая вопросы, связанные с гарнизоном позднеантичного Херсонеса, К. Цукерман отрицает историческую достоверность сведений труда Константина Багрянородного «Об управлении империей», полностью игнорируя достижения современной отечественной историографии. Анализируя эпиграфические памятники III — IV вв., К. Цукерман допускает ряд ошибок и неточностей. Нельзя признать удачной и попытку К. Цукермана восстановить в двух херсонесских надписях совместное упоминание I Италийского легиона и легиона II Herkuliae, которые находились в подчинении дуксов двух разных провинций — Мезии II и Скифии.
Допущенные К. Цукерманом грубые ошибки при анализе источников и полное игнорирование того, что сделано отечественной историографией по затронутой проблеме, не позволяет принять его концепцию о римском военном присутствии в позднеантичном Херсонесе. Поэтому точка зрения о союзных отношениях этого центра с Восточно-Римской империей, которая разработана украинскими специалистами, по-прежнему продолжает оставаться наиболее аргументированной. The paper about bishops and garrison of the Chersonese in the 4th cent, written by K. Tsukerman and published in the 4th issue of collected papers «Proceedings on Archaeology, History and Ethnography of Tauris» in 1994 is discussed. K. Tsukerman made a thorough analysis of sources (a synaxaric paper of the 22nd of December and a list of participants of the 2nd Occumenical council in 381), which has permitted him to specify legendary date of «The Lives of Holy Chersonese Bishops» putting the period of their activity forward for some ten years. His conclusions, however, cannot be treated as unique ones as the problem in the home historiography was developed by I. Franko and for the latest period was elucidated in more than ten scientific papers which are, apparently, unknown to K. Tsukerman.
Analyzing certain problems related to a garrison of the late antique Chersonese, K. Tsukerman denies historical reliability of information provided by the treatise of Konstantin Bagryanorodny «About Management of the Empire» and so, completely ignores achievements of the present home historiography. Tsukerman makes some errors when analyzing epigraphic relics of the 3d-4th cent. It cannot be treated as successful his attempt to restore combined mentioning of the 1st Italian legion and 2nd legion Herculiae in two Chersonese inscriptions, as they were subordinated to dukes of two different provinces: Mesia II and Scythia.
Flagrant errors made by K. Tsukerman in the analysis of sources and complete disregard of achievements of home historiography in the problems mentioned do not allow adopting his conception about the Roman military presence in the late antique Chersonese. That is why the idea on the allied relations existed between that centre and Eastern-Roman Empire developed by the Ukrainian specialists still remains the most well reasoned one.